Maternal Rat Diabetes Mellitus Deleteriously Affects Insulin Sensitivity and Beta-Cell Function in the Offspring - Abdel-Baset M. Aref; Osama M. Ahmed; Lobna A. Ali; Margit Semmler (Journal of Diabetes Research)
This study was designed to assess the effect of maternal diabetes in rats on serum glucose and insulin concentrations, insulin resistance, histological architecture of pancreas and glycogen content in liver of offspring. The pregnant rat females were allocated into two main groups: normal control group and streptozotocin-induced diabetic group. After birth, the surviving offspring were subjected to biochemical and histological examination immediately after delivery and at the end of the 1st and 2nd postnatal weeks. In comparison with the offspring of normal control dams, the fasting serum glucose level of offspring of diabetic mothers was significantly increased at the end of the 1st and 2nd postnatal weeks. Serum insulin level of offspring of diabetic dams was significantly higher at birth and decreased significantly during the following 2 postnatal weeks, while in normal rat offspring, it was significantly increased with progress of time. HOMA Insulin Resistance (HOMA-IR) was significantly increased in the offspring of diabetic dams at birth and after 1 week than in normal rat offspring, while HOMA insulin sensitivity (HOMA-IS) was significantly decreased. HOMA beta-cell function was significantly decreased at all-time intervals in offspring of diabetic dams. At birth, islets of Langerhans as well as beta cells in offspring of diabetic dams were hypertrophied. The cells constituting islets seemed to have a high division rate. However, beta-cells were degenerated during the following 2 post-natal weeks and smaller insulin secreting cells predominated. Vacuolation and necrosis of the islets of Langerhans were also observed throughout the experimental period. The carbohydrate content in liver of offspring of diabetic dams was at all-time intervals lower than that in control. The granule distribution was more random. Overall, the preexisting maternal diabetes leads to glucose intolerance, insulin resistance, and impaired insulin sensitivity and β-cell function in the offspring at different postnatal periods.